Mucosal barrier injury as an independent risk factor for laboratory-confirmed bloodstream infection in patients with hematological malignancies: a real-world study - Mengna Liu; Xi Jiang; Yingqi Pi; Mingming Chen; Xiuqin Ren; Xinlu Dai; Yixian Wu; Yanrong Guo; Xinyi Zhang; Xiaoying Xie; Zhaofan Luo (European Journal of Medical Research)
Abstract Background Hematological malignancy (HM) patients are at high risk of bloodstream infections (BSIs) due to chemotherapy-induced mucosal barrier injury (MBI), invasive procedures, and prolonged antimicrobial exposure. While conventional nosocomial infection paradigms emphasize catheter-related biofilms, emerging evidence highlights the role of disrupted oral/gut microbiomes in bacterial translocation. This study aimed to identify risk factors for bacteremia secondary to MBI following chemotherapy in patients with HM. Methods A single-center, retrospective analysis of 72 HM patients, including 24 with mucosal barrier injury laboratory-confirmed bloodstream infection (MBI-LCBI), 22 with non-MBI-LCBI, and 26 controls without BSIs, was conducted. Microbiology profiles, resistance patterns, and risk factors for BSIs were analyzed. Results All MBI-LCBI patients had significantly longer neutropenia duration than non-MBI-LCBI patients did (median 6.5 vs. 3.0 days, p = 0.013). Multivariate analysis identified MBI as an independent risk factor for BSIs (OR = 11.467, 95% CI1.287–102.170). Prolonged hospitalization (> 30 days) was associated with BSI occurrence (OR = 6.758, 95% CI 1.102–41.440) and neutropenia duration (OR = 1.112, 95% CI 1.014–1.220). Significant differences in pathogen distribution were observed between groups: Escherichia coli, Klebsiella pneumoniae, and viridans group streptococci predominated in the MBI-LCBI group, whereas Pseudomonas aeruginosa and Staphylococcus spp. were common in the non-MBI-LCBI group. Carbapenem resistance remained below 20% for key gram-negative pathogens. Conclusions MBI is an independent risk factor for BSI in HM patients, highlighting the need for targeted mucosal protection strategies. MBI-LCBI pathogens primarily originate from the gut/oral flora, and are distinct from catheter-related infections. Carbapenems are recommended for empirical therapy, yet resistance surveillance remains essential.